Deciphering the critical role of interstitial volume in glassy sulfide superionic conductors - Han Su; Yu Zhong; Changhong Wang; Yu Liu; Yang Hu; Jingru Li; Minkang Wang; Longan Jiao; Ningning Zhou; Bing Xiao; Xiuli Wang; Xueliang Sun; et al. (Nature Communications, 2024)
Abstract Sulfide electrolytes represent a crucial category of superionic conductors for all-solid-state lithium metal batteries. Among sulfide electrolytes, glassy sulfide is highly promising due to its long-range disorder and grain-boundary-free nature. However, the lack of comprehension regarding glass formation chemistry has hindered their progress. Herein, we propose interstitial volume as the decisive factor influencing halogen dopant solubility within a glass matrix. We engineer a Li3PS4-Li4SiS4 complex structure within the sulfide glassy network to facilitate the release of interstitial volume. Consequently, we increase the dissolution capacity of LiI to 40 mol% in 75Li2S-25P2S5 glass. The synthesized glass exhibits one of the highest ionic conductivities among reported glass sulfides. Furthermore, we develop a glassy/crystalline composite electrolyte to mitigate the shortcomings of argyrodite-type sulfides by utilizing our synthesized glass as the filler. The composite electrolytes effectively mitigate Li intrusion. This work unveils a protocol for the dissolution of halogen dopants in glass electrolytes.